Keterlibatan Lintas Sektor pada Konvergensi Kebijakan Percepatan Penurunan Stunting di Kota Padang - Fadlan, Rayhan; Yusran, Rahmadani (Journal of Civic Education, 2024)
This study investigates the role of Local Apparatus Organizations (OPDs) in the convergence of policies aimed at accelerating stunting reduction in Padang City. Employing a descriptive qualitative approach, the research reveals that policy convergence is manifested through OPD engagement in the stages of planning, implementation, and coordination, with the goal of fostering synergy in the fight against stunting. However, despite the expressed cross-sectoral commitment, the presence of sectoral egos and differing interpretations among agencies pose significant challenges to effective implementation. Additionally, constraints such as limited human resources, budgetary shortfalls, inadequate coordination, and lack of discipline among OPDs contribute to the suboptimal performance of the program. The findings underscore the need for follow-up actions and a more profound comprehension of policy convergence to enhance the success of these initiatives.